Dependency Theory: developments and contributions to international relations - Vitor Lengruber (Ибероамериканские тетради)
A number of scholars have recently pointed out that International Relations (IR) is a discipline mostly formulated from the modern European political experience and philosophical developments, although it proposes to address international issues. Various critics point to the Eurocentric nature of IR theory (IRT), or argue that Europe’s modern history cannot properly elucidate the past and the present of nonWestern regions. In an attempt to turn IR into a truly international discipline, scholars from non-Western regions have provided their own local contributions (e.g. concepts, historical experiences, philosophies, etc.). This intellectual movement also aims to offer a better explanation of their respective regions. Although Latin America’s Dependency Theory is not widely recognized as a proper IRT itself, this paper argues that it maycontribute to it. The article is divided into three sections. The first section elaborates two criticisms of the Eurocentric approach to International Relations and its theories. The second briefly presents the thinking of the Dependentistas (Fernando Henrique Cardoso and Enzo Faletto, Ruy Marini, and Samir Amin, although the latter is French-Egyptian), as well as that of the ECLA. And the third argues that Dependency Theory might contribute to IRT in three ways: (1) by acknowledging that problems, and thus interests, are not homogeneously universal, it emphasizes the need of local solutions for local problems; (2) it is sensitive to non-traditional actors, such as multinational companies and domestic economic groups; (3) it understands the international arena as hierarchically constituted by a core-periphery rivalry